1980
DOI: 10.1515/znb-1980-1118
|View full text |Cite
|
Sign up to set email alerts
|

Salts of Ferricinium Cation and its Homologues: NMR Investigation, II EPR and NMR Spectra of sym-Polymethyl Substituted Ferricinium Cations

Abstract: Abstract The EPR, 1H and 13C NMR spectra of methylferricinium hexafluorophosphates, [(MenCp)2Fe]PF6, n = 0-5, have been recorded. HFS constants have been estimated for all the ligand atoms. The general pattern of the spin density distribution is shown to depend on the superposition of the various mechanisms of spin delocalization. For the majority of the cations the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The values of the g -tensor are g ⊥ = 1.61 and g ∥ = 3.86, with the “parallel” value representing the situation of the magnetic field aligned normal to the cyclopentadienyl rings. We note that this anisotropy is smaller than the one reported , for the ferricenium cation, with values of g ⊥ = 1.3 and g ∥ = 4.4. The substitution of the ferrocenophane in Fcp-Nb + should not influence the distortion of the cyclopentadienyl rings.…”
Section: Resultscontrasting
confidence: 73%
“…The values of the g -tensor are g ⊥ = 1.61 and g ∥ = 3.86, with the “parallel” value representing the situation of the magnetic field aligned normal to the cyclopentadienyl rings. We note that this anisotropy is smaller than the one reported , for the ferricenium cation, with values of g ⊥ = 1.3 and g ∥ = 4.4. The substitution of the ferrocenophane in Fcp-Nb + should not influence the distortion of the cyclopentadienyl rings.…”
Section: Resultscontrasting
confidence: 73%
“…Negative spin densities in the ligand π orbitals were calculated from the shift tensor anisotropies for [(C 5 Me 5 ) 2 Cr] + and [(C 5 Me 5 ) 2 Mn] + , as expected for a sandwich compound with less than six d electrons (vide supra). For the cations mentioned so far, the g -factor anisotropy is small 25a,b so that the analysis is a good approximation 5c. A different case is the cation [(C 5 Me 5 ) 2 Fe] + where the g -factor anisotropy is large and where the quantitative analysis is hampered because additional anisotropic shift contributions come into play.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all Cp protons in the cation of 16 have negative spin density and positive contact shifts relative to the shifts of the corresponding neutral biferrocene. Making a comparison of the sign of contact shifts of the ethyl substituents attached to the Fe(III) 1‘,3‘-diethylferrocenium moiety with that of the contact shifts of the Cp protons in 16 leads to the conclusion that the unpaired electron density in this ferrocenium unit is delocalized in π Cp orbitals, as found in ferrocenium and 1,1‘-dimethylferrocenium ions. The π-polarization effect in metallocenes was first discussed by Levy and Orgel in 1960. It was suggested that the unpaired π electron in the Cp orbitals polarizes the C−H σ bond.…”
Section: Resultsmentioning
confidence: 99%
“…This would lead to negative spin density and positive contact shifts at the protons in metallocenes. Rettig, 29 Materikova, 30 and Kurbanov 31 reported the 1 H and 13 C NMR spectra of ferrocenium and 1,1′dimethylferrocenium ions. For the 1,1′-dimethylferrocenium cation, the negative spin density at Cp protons and the positive spin density at methyl protons led the authors to propose the π-skeleton spin delocalization.…”
Section: Resultsmentioning
confidence: 99%